Effect of Roller Modification on Shear Stress of Cylindrical Roller Bearing under Flooded/Stared Oil Condition - Wenjie Wang; Ming Qiu; Yanfang Dong; Hui Du; Tuanliang Lu; Dawei Zhou (Jixie chuandong)
The NJ2205 cylindrical roller bearing is taken as the analysis object， and roller modeling is carried out through ANSYS software to analyze the "edge effect" problem between roller and raceway under the conditions of flooded oil and stared oil， and the shear stress distribution of roller and raceway is compared and analyzed under the conditions of unmodified， full convex modification and logarithmic modification. The results show that under the condition of radial load is 11.45 kN and speed is 4 000 r/min， the shear stress in the direction of the roller generatrix under flooded oil condition is less than that of stared oil condition， the shear stress in the non-repair mode is the largest， and the logarithmic repair mode. The shear stress is the smallest， and the fully convex repair under oil-rich and spent oil reduces by 17.02% and 10.58% respectively compared to the unrepaired shape， and the logarithmic repair reduces by 32.95% and 17% respectively compared to the unrepaired shape. Therefore， the roller of NJ2205 cylindrical roller bearing adopts log modification curve can effectively reduce the shear stress.